Pengawasan Dalam Pemungutan Retribusi Jasa Umum Atas Pelayanan Kesehatan Pada Uptd Puskesmas Ratu Jaya Tahun 2023 - Rosdiana, Dika; Selvi, Selvi (Jurnal Ilmu Administrasi Publik, 2024)
This study aims to analyze how supervision in collecting public service levies on health services at UPTD Puskesmas Ratu Jaya, to analyze the obstacles to supervision in collecting public service levies on health services at UPTD Puskesmas Ratu Jaya, and to analyze the efforts made in overcoming supervision obstacles in collecting public service levies on health services at UPTD Puskesmas Ratu Jaya. This method and type of research is descriptive qualitative. This type of research is based on the place of research, namely field research, which is research by conducting observations in the field to explore further information, namely through informants BLUD Treasurer, Accounting Officer, Cashier, Registration Officer and patients. The results showed that the theory of supervision implemented at UPTD Puskesmas Ratu Jaya has not been maximally implemented, due to obstacles, namely limited human resources, inadequate systems and technology, lack of implementation of standard operating procedures that have been set, time management. And there are efforts to overcome these obstacles by implementing standard operating procedures, conducting routine inspections, improving the simpus depok system, adding specialized staff and conducting internal and external audits.